Torefaksi Batang Sawit : Pengaruh Kondisi Proses Terhadap Nilai Kalor Produk Torefaksi - Monika Shecilia; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Oil palm trunk can be used as alternative energy source by torrefaction process. Torrefaction is a treatment process of biomass into solid fuel by heating within temperature range of 200-300oC in an inert environment. This research aims to result solid fuel from oil palm trunk through torrefaction, to study the effect of process variabel interaction and to study the characteristic of solid fuel resulted. Torrefaction of oil palm trunk was using fixed bed horizontal reactor with temperature (225-275oC), time (15-45 minutes) and nitrogen flow rate (50-150 ml/min). Responses resulted was calorific value and the result obtained for calorific value was 17.908 – 21.800 kJ/kg. The most affecting factor significantly towards the responses was temperature of torrefaction that followed by time and nitrogen flow rate. In optimum condition (temperature of 240,53°C for 15 minutes with nitrogen flow rate of 50 ml/menit) was obtained the optimum value of response for calorific value by 19.180,54 kJ/kg.Keywords: oil palm trunk, response surface methodology, solid fuel, torrefaction.